Characterization of RF signal behavior for the use in indoor human presence detection - Ali, Mahamat Mahamat; Habaebi, Mohamed Hadi; bin Aliasaa, Nazrul Arif; Islam, Md Rafiqul; Hameed, Shihab A (Asian Research Publishing Network (ARPN), 2015)
This paper presents a method or technique that identifies physical intrusion detection in an indoor environment that is based on received signal strength indicator (RSSI) on radio frequency identification. The objective of this paper is two folds. Firstly, is to characterize the signal behavior in an indoor environment using statistical measures. Secondly, is to identify the existence of a human presence inside a contained environment (e.g., room). The objective is to use simple means like the recorded readings of the received signal strength indicator (RSSI). The characterization was observed during three distinctive time intervals, namely; empty room, with human presence, and transitional period during link crossings. The experiment was repeatedly conducted for 5 minutes to validate the averaged results. In order to emulate real-life environment, experiments were conducted using Zigbee-compliant iris mote XM2110 and MIB510 programming boards with transmitter and receiver antennas, and interfaced using TinyOS software on Linux. Our results show that there are distinctive statistical features that can utilized as flags to classify the three cases stated above, empty room, occupied and link being crossed. These results motivate the design of alarm system to detect human presence using RSSI statistics only.